T is for tutu : a ballet alphabet - Rodriguez, Sonia; Browning, Kurt.; Ong, Wilson (Ann Arbor, MI : Sleeping Bear Press, 2011)
A rhyming alphabet that identifies things associated with ballet, and provides background information on each one.
6.0
K-3
Keywords: Ballet -- Juvenile literature; Alphabet books -- Juvenile literature; Ballet; Alphabet; Ballet; Alphabet; Picture books for children